High Availability Controller Software Defined Network Menggunakan Heartbeat dan DRBD - Maskur Purwiadi; Widhi Yahya; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Network model architecture that used nowadays are difficult to apply a new protocol because it depends upon vendor, so it appeared a concept that manage network systemperformance through software named Software Defined Network. SDN separating data-plane and control-plane in network devices such as router and switch, so that programming network devices may be done centrally through a controller.A controller manage forwarding table switch which forwarding the flow of communication package.If a controller goes offlinea switch not be able to forwarding the flow of communication package from a device to other devices. So it needs high availabillity controller mechanism to be able to maintain the availability of a controller so the communication package can be arrive. High availability controller can be done by mechanism failover use Heartbeat and DRBD.Testing in this research done with planned downtime methods. The test results that obtained from the average downtime of POX controller when failover process is 23 seconds, and 59,6 seconds when failback process, while Opendaylight controller took time 195 seconds for failover process and 219 seconds for faillback. This method is a good enough, where the more features run in a controller the longer time downtime will produced.